ANALISIS TINGKAT PARTISIPASI ANGKATAN KERJA BERDASARKAN KEGIATAN EKONOMI MASYARAKAT DESA TEGALSARI KECAMATAN TEGALSARI KABUPATEN BANYUWANGI TAHUN 2015 - Vina Shofia Nur Mala; Bambang Suyadi; Retna Ngesti Sedyati (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
Tegalsari Village is one of the villages is in southern district Banyuwangi.The Village is quite far from the city center and the education level of community lower to question is how villagers Tegalsari participate in the workplace . This study aims to determine how much the labor force participation rate (LFPR) Village community Tegalsari, Tegalsari District of Banyuwangi in 2015, to determine the dominant economy sectors of society and describe how labor force participation rate in the village Tegalsari. Determining where the research using purposive area. For determine respondents in this research uses a method of the population purporsive that is working age in village Tegalsari in the informal sector which includes primary sector (agriculture,farm), secondary sector (home industry, trade) and tertiary sector (services). Data collection methods used consisiting of the: observation, survey, interview and documents. The results of the analysis of data obtained by the labor force participation rate in the village Tegalsari in 2015 higher by 70%, which includes 67% LFPR in the informal sector and 3% in the formal sector. Of the 67% LFPR in the informal sector, 60% of the LFPR in the primary sector, 6% LFPR in the secondary sector and 1% in the tertiary sector.